RNA-binding protein HuR enhances p53 translation in response to ultraviolet light irradiation - Mazan-Mamczarz, Krystyna (National Academy of Sciences, 2003)
Exposure to short-wavelength UV light (UVC) strongly induces p53 expression. In human RKO colorectal carcinoma cells, this increase was not due to elevated p53 mRNA abundance, cytoplasmic export of p53 mRNA, or UVC-triggered stabilization of the p53 protein. Instead, p53 translation was potently enhanced after UVC irradiation. The 3′ UTR of p53 was found to be a target of the RNA-binding protein HuR in a UVC-dependent manner in vitro and in vivo. HuR-overexpressing RKO cells displayed elevated p53 levels, whereas cells expressing reduced HuR showed markedly diminished p53 abundance and p53 translation. Our results demonstrate a role for HuR in binding to the p53 mRNA and enhancing its translation.